Botanical drug clinical trial: Common issues and future options - Yu Sun; Jiahua Qian (Elsevier, 2021)
In order to understand this disparity between human use and drugs approved by regulatory agencies, we analyzed botanical drug clinical trials registered at ClinicalTrial.gov to detect trends in current trials and guide future trials. A total of 195 botanical drug clinical trials were registered from 2016 to 2019, of which 81 are phase II or phase II/III. 95% of all phase II and II/III studies were designed with 100 or less participants per arm, indicating a more observational nature due to the limited power to detect differences in outcomes between treatment and control groups. Due to the limited number of participants, efficacy outcome from results may be highly subjective. 14% of the total trials were phase I studies. For botanical drugs with well-documented or extensive history of human use, phase I may not provide significant additional information, and may, therefore, not be necessary. For the trial design, we suggest added-on studies when botanical drugs are used as part of a combination treatment. Additionally, we believe standardized data collection methods and criteria are critical to utilizing the vast collection of human experience as quality evidence to support regulatory approval.